2014
DOI: 10.2147/ppa.s72875
|View full text |Cite
|
Sign up to set email alerts
|

Superselective arterial embolization of the superior mesenteric artery for the treatment of gastrointestinal hemorrhage following allogeneic hematopoietic stem cell transplantation

Abstract: Superselective arterial embolization is a common therapeutic procedure for cases of visceral hemorrhage. However, until now, it has not been applied in the treatment of gastrointestinal (GI) hemorrhage caused by acute graft-versus-host disease (GVHD) after allogeneic hematopoietic stem cell transplantation. We describe a case presenting with persistent GI bleeding associated with acute GVHD successfully treated by superselective arterial embolization of the superior mesenteric artery with gelatin sponge after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Continuous infusion of octreotide has been studied for the treatment of GVHD-related gastrointestinal bleeding, but its efficacy is lost when the drug is discontinued 172 . In the setting of ongoing bleeding that cannot be managed with conservative approaches, cases of successful arterial embolization have been reported 173 . Another technique is intra-arterial platelet transfusion 174 .…”
Section: Managementmentioning
confidence: 99%
“…Continuous infusion of octreotide has been studied for the treatment of GVHD-related gastrointestinal bleeding, but its efficacy is lost when the drug is discontinued 172 . In the setting of ongoing bleeding that cannot be managed with conservative approaches, cases of successful arterial embolization have been reported 173 . Another technique is intra-arterial platelet transfusion 174 .…”
Section: Managementmentioning
confidence: 99%
“…Surgical literature has demonstrated that surgical intervention provides, at best, temporarily cessation of hemorrhage in patients with UGIB related to GVHD. [40][41][42] While gastrointestinal hemorrhage following bone marrow transplantation is relatively low, 10%, 43,44 acute UGIB from GVHD has reported mortality rates as high as 30 to 60%. 43,45 While UGIB can be effectively controlled with transcatheter arterial embolization, patients with bleeding related to GVHD should be approached with treatment strategies that take into consideration the diffuse nature of this disease and the near universal presence of severe refractory thrombocytopenia.…”
Section: Procedural Outcomes and Complicationsmentioning
confidence: 99%